Research progress in overlap syndrome associated with systemic lupus erythematosus and its management strategies - Zhen FENG; Qing GUO; Hui XIONG (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2023)
Overlapping syndrome is a syndrome that meets the criteria for at least two connective tissue diseases. When systemic lupus erythematosus (SLE) overlaps with systemic sclerosis (SSc), dermatomyositis/polymyositis, Sjogren's syndrome (SS), rheumatoid arthritis (RA), and other diseases, the lack of specific serological indicators and clinical manifestations can result in missed diagnosis and/or misdiagnosis, leading to life-threatening in severe cases. Early diagnosis and treatment of overlap syndrome can help alleviate the impact on patients' quality of life and improve the prognosis. This article reviews the research progress in this disorder and its management strategies. Although there is currently limited research on SLE related overlap syndrome, its clinical manifestations and immunological characteristics are strongly related to the overlapping diseases. Specific tests and examinations in time can facilitate the diagnosis and treatment of overlap syndrome.